PENDEKATAN STRATEGIS DALAM PENANAMAN NILAI DISIPLIN PADA SISWA SEKOLAH DASAR SELAMA PANDEMI COVID-19: STUDI KASUS DI MIS NURUL HIDAYAH KOTA RAJA - Sari, Nita Yusfa (Titik Fokus Karya, 2024)
This study aims to describe the strategy for instilling the value of disciplined character in fourth-grade students of MIS Nurul Hidayah Kota Raja during the Covid-19 pandemic. The background of this research is the importance of discipline in learning, especially during the pandemic when the teaching process had to be conducted online and offline. The research method used is a qualitative field research approach. Data were collected through interviews, observations, and documentation. The subjects of this study were the head of the madrasa, fourth-grade teachers, and fourth-grade students of MIS Nurul Hidayah Kota Raja. The results showed that the strategy for instilling disciplined character values was carried out through three stages: planning, implementation, and evaluation. In planning, teachers developed plans to instill discipline through both online and offline learning. The implementation emphasized three main aspects: time discipline, social attitude discipline, and discipline in worship. Evaluation was conducted to assess the effectiveness of the strategies implemented. The main supporting factors were the role of parents and teachers, while the inhibiting factors included a lack of parental attention and difficulties for students to adapt to online learning.